الهيدروجيولوجيا الكارستية ( والمياه الجوفية في الصخور الكلسية ) - محمود نبع (Tishreen University, 2019)
يتناول البحث الهيدروجيولوجيا الكارستية, وأنواع الصخور الكلسية, والصخور الحاوية على الماء ويقوم بدراسة التركيب الكيميائي, والنفوذية, والمسامية, والذوبان, لهذه الصخور, والعوامل الفيزيائية, والكيمائية التي تؤدي إلى انحلالها وذوبانها, وأهمية هذا الانحلال وما ينتج عنه من فجوات وشقوق وتجاويف, ودراسة هذه الشقوق وأصلها وعوامل تكوينها وأهميتها وتأثيرها في الصخور الكلسية, ودراسة الميزات الهيدروجيولوجية للصخور الكلسية, بدراسة جريان المياه الباطنية وأنواع هذا الجريان وميزاته, وتأثير الشقوق والتجاويف والفجوات في هذا الجريان, ودراسة المناطق الهيدروجيولوجية من منطقة الإشباع, ومنطقة التهوية, والسطح الحر, ودراسة الميزات الليتولوجية, والستراتيغرافية, ودور التبدلات في شكل الأرض, وما لهذه الدراسة من دور كبير في الهيدروجيولوجيا الكارستية.   This article deals with karst hydrogeology which studies the kinds of Oolitic rocks and water conservation that has chemical embossing permeability, porosity and fluxing capability. It also studies physical and chemical factors which lead to the dissolution and dissolve of Oolitic rocks, this dissolution and what produces from gulfs, cleavages and cavities, the study of these cleavages, their origin, composition factors, importance and their effect in Oolitic rocks. This article also focuses on the study of hydro geological advantages of the Oolitic rocks by studying ground water flowing and kinds of this flowing, advantages, effect of cleavages, cavities and gulfs in this flowing. It also deals with the study of the hydro geological areas, from zone of saturation, zone of aeration. Then it focuses on the study of lithogical and strotigrophical advantages and the role of the changes in the shape of Earth and what a great role this study has in the karst hydrogeology.